Analisis Kesalahan Bacaan Surah Al-Qori’ah Siswi Kelas X SMAN 1 Lawang Malang (Perspektif Fonetik Bahasa Arab) - Thasya, Tiasa; Choridah, Rifka Arifatul; Fauzi, Ahmad; Alfani, Achwan; Rosyidi, Abdul Wahab (Jurnal Al-Mashadir: Journal of Arabic Education and Literature, 2024)
This study aims to determine phonetic errors in reading the Al-Quran Surah Al-Qari’ah in grade 10 students of SMAN 1 Lawang. The method used in this study is descriptive qualitative with the help of short YouTube videos uploaded by these students. The results of this study are phonetic errors that occur due to the inability of students to distinguish 2 sounds that have almost the same sound, some sounds are difficult to pronounce because they are not found in the Indonesian alphabet, and the inaccuracy of the reader in pronouncing the makharijul letters. Therefore, students should make habituation in learning about how to pronounce the hijaiyah letters makharijul which are not found in the Indonesian alphabet, pay attention to the articulation of words when pronouncing a letter, and practice so they can distinguish 2 sounds that are almost the same.